Fibroblas Terkait Kanker dan Dampaknya terhadap Kelangsungan Hidup Keseluruhan pada Karsinoma Urotelial Kandung Kemih: Suatu Tinjauan Sistematis: Cancer-Associated Fibroblasts and Their Impact on Overall Survival in Bladder Urothelial Carcinoma: A Systematic Review - Kurnia, Jodii Arlan; Mardenanta, Vico (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Background: Bladder urothelial carcinoma (BUC) remains a common urologic malignancy with substantial mortality. The tumor microenvironment (TME), particularly cancer-associated fibroblasts (CAFs), promotes extracellular matrix remodeling, angiogenesis, immune evasion, and treatment resistance, suggesting CAFs may serve as prognostic and predictive biomarkers. Objective: To evaluate the association between CAFs and overall survival (OS) in BUC and identify clinically relevant CAF-related markers. Methods: A PRISMA-guided systematic review was performed using PubMed, Cochrane Library, Taylor & Francis, ProQuest, Scopus, and EMBASE (2015–2025). Eligible human studies assessing CAFs/CAF-signatures in BUC were included. Risk of bias was assessed using ROBINS-I. Results: Nine studies were included. Across cohorts, elevated CAF abundance or CAF-related markers consistently correlated with poorer outcomes. High CAF infiltration in TCGA-BLCA was associated with reduced OS (p=0.003) and advanced stage (p<0.001). Stromal markers such as FAP (HR=2.06) and PDGFRβ (HR=1.75) predicted worse OS, with FAP-dominant phenotypes showing the lowest survival. myCAF- and iCAF-high subtypes were linked to shorter OS (e.g., iCAF cluster p=0.024). Multiple CAF-based gene signatures (e.g., 7-gene models) stratified mortality risk (multivariate HR up to 3.51; AUC 0.88). COL10A1 overexpression also predicted inferior OS. A fibroblast-related gene index (FRGI) showed strong performance in ICI-treated patients (1-year OS AUC=0.95) and was enriched in non-responders. Conclusion: CAF abundance and subtype composition are robust adverse prognostic indicators in BUC and show promise for risk stratification and treatment decision support, particularly for immunotherapy responsiveness.